Construction and stable gene expression of AGR2xPD1 bi-specific antibody that enhances attachment between T-Cells and lung tumor cells, suppress tumor cell migration and promoting CD8 expression in cytotoxic T-cells - Debmalya Roy; Guo-Song Liu; Aru Zeling Wang; Bingjie Zhou; Fakhar-; Ghulam Raza; Siva Bharath Merugu; Dhahiri Saidi Mashausi; Dawei Li; Bo Zhao (Elsevier, 2023)
There has been a substantial and consistent rise in the number of clinical trials to develop advanced and potent bispecific antibodies (BsAb) over the past two decades with multiple targets to improve the efficacy or tissue specificity of monoclonal antibodies (mAb) treatment for diseases with multiple determining factors or widely-expressed targets. In this study, we designed and synthesized BsAb AGR2xPD1 targeting extracellular AGR2, a paracrine signal, and PD1, an immune checkpoint protein. Our design is intended to use AGR2 binding to guide PD1 targeting for AGR2+cancer. We used this construction to produce AGR2xPD1 BsAb by generating clonally selected stable 293F cell line with high expression. Applying this BsAb in a T cell-Tumor cell co-culture system showed that targeting both PD1 and AGR2 with this BsAb induces the attachment of TALL-104 (CD8+ T-lymphocytes) cells onto co-cultured H460 AGR2+ Lung tumor cells and significantly reduces migration of H460 cells. T-cell expression of CD8 and IFNγ is also synergistically enhanced by the AGR2xPD1 BsAb treatment in the AGR2+H460 co-culture system. These effects are significantly reduced with AGR2 expression negative WI38 cells. Our results demonstrate that the AGR2xPD1 BsAb could be a potential therapeutic agent to provide better solid tumor targeting and synergetic efficacy for treating AGR2+ cancer by blocking AGR2 paracrine signaling to reduce tumor survival, and redirecting cytotoxic T-cells into AGR2+ cancer cells.